“What is the cocoon but a dark cabinet?”: Benjamin O. Flower, Print Culture and the Legitimisation of Fringe Science in the 1890s - Marin-Lamellet, Jean-Louis (Mémoires du livre / Studies in Book Culture, 2014)
This study examines how Boston editor and publisher Benjamin O. Flower used print culture to circulate and legitimise fringe science in the 1890s. Using evolutionary theory as a template for progress, he considered hypnotism and spiritualism – what he called “psychical research” ‒ as the natural extension of environmental meliorism from the visible to the invisible. This article examines the transatlantic dimension of the idea of a “science of mind” and how it led Flower to formulate a spiritual and materialist conception of the influence of print. It describes the rhetorical strategies, the scientific procedures and institutionalisation policies he adopted in his quest to naturalise the invisible and subject it to the purview of methodological naturalism. Finally, it explores the epistemological foundations of Flower’s redefinition of the boundaries of legitimate science.